Analysis of RNA-Seq, DNA Target Enrichment, and Sanger Nucleotide Sequence Data Resolves Deep Splits in the Phylogeny of Cuckoo Wasps (Hymenoptera: Chrysididae). Issue 1 (4th January 2021) - Pauli, Thomas; Meusemann, Karen; Kukowka, Sandra; Sann, Manuela; Donath, Alexander; Mayer, Christoph; Oeyen, Jan Philip; Ballesteros, Yolanda; Berg, Alexander; van den Berghe, Eric; Escalona, Hermes E; Guglielmino, Adalgisa; et al.
Abstract: The wasp family Chrysididae (cuckoo wasps, gold wasps) comprises exclusively parasitoid and kleptoparasitic species, many of which feature a stunning iridescent coloration and phenotypic adaptations to their parasitic life style. Previous attempts to infer phylogenetic relationships among the family's major lineages (subfamilies, tribes, genera) based on Sanger sequence data were insufficient to statistically resolve the monophyly and the phylogenetic position of the subfamily Amiseginae and the phylogenetic relationships among the tribes Allocoeliini, Chrysidini, Elampini, and Parnopini (Chrysidinae). Here, we present a phylogeny inferred from nucleotide sequence data of 492 nuclear single-copy genes (230, 915 aligned amino acid sites) from 94 species of Chrysidoidea (representing Bethylidae, Chrysididae, Dryinidae, Plumariidae) and 45 outgroup species by combining RNA-seq and DNA target enrichment data. We find support for Amiseginae being more closely related to Cleptinae than to Chrysidinae. Furthermore, we find strong support for Allocoeliini being the sister lineage of all remaining Chrysidinae, whereas Elampini represent the sister lineage of Chrysidini and Parnopini. Our study corroborates results from a recent phylogenomic investigation, which revealed Chrysidoidea as likely paraphyletic. Graphical Abstract: